Emotional Intelligence, Humor Styles and Personality Traits as Determinants of Coping Behavior, Dysfunctional Attitude and Perceived Stress - Kaur, Tavleen (My University, 2019)
Humans put enormous efforts to keep stress at a distance and the foremost tool put to use is humor. Researchers have sufficiently emphasized on the importance of coping in demanding life circumstances. Individuals who are emotionally intelligent are better at coping, and therefore have lesser tendency to have dysfunctional attitude. Personality like a mother of all has a role in shaping an individual’s life and in some way dictates as to how an individual copes, how he faces stress and whether or not has dysfunctional attitude. The aforementioned variables have been studied individually by many researchers. However, it is interesting how these variables are interlinked. The present study aims to analyze the relationship between emotional intelligence, humor styles, personality traits and coping behavior, dysfunctional attitude and perceived stress. The study included 120 participants (N=120) of the age range, 18-25 years, from which sixty were males (N=60) and sixty females (N=60). The present study is a humble effort to analyze the relationship between the above mentioned variables with the help of correlation and regression.
Keywords: Emotional intelligence; dysfunctional attitude; Personality traits; humor styles; Coping Behaviour